ERGONOMIC REQUIREMENTS FOR ON-SCREEN EDUCATIONAL INFORMATION - N. A. Kloktunova; S. V. Venig; V. A. Solovyova (Высшее образование в России)
The different possibilities of delivery the educational information raise the new questions to the educational community. Among them not only the question concerning the creating of modern interactive technologies ‘student-teacher’ but also the question about the appropriate delivery forms that could be used for the educational information and would activate students’ cognitive processes. The most attention should be paid to the information on the screen because the way of thinking and methods that students use to read are changing. So, in this work the existing rules of delivering information are considered as well as the regularities of perception on-screen information. A list of ergonomic rules based on the analyzed material is suggested. The friendly E-environment created with using of these rules would contribute to the improvement of the students’ overall performance in working with texts.